High‐frequency electric‐motor modelling for conducted CM current prediction in adjustable speed drive system. Issue 7 (3rd May 2018) - Bi, Chuang; Jia, Kelin; Wu, Yingzhe; Dong, Liang; Li, Hui; Yao, Weizheng; Liu, Gang; Zhang, Hailong
Abstract : This study presents a novel high‐frequency three‐phase permanent magnet synchronous motor (PMSM) model to predict the common‐mode (CM) current and CM voltage in a pulse‐width modulation inverter‐fed adjustable speed drive systems. Parameters of the model are calculated based on the measured CM impedance, applying vector fitting method. The model‐calculated CM impedance is compared with the experimental impedance measured on a 3 kW PMSM with the star‐winding connection, which has shown considerable accuracy at a frequency range of 100 Hz–10 MHz. The frequency‐domain analysis of CM voltage and CM current is then predicted by using the proposed circuit model in MATLAB/Simulink, which gives good agreement between calculated and the measured results.